The impact of metacognitive-based learning strategies on enhancing students' decision-making and cognitive dissonance - Surya Abadi, Ida Bagus Gede; Widiana, I Wayan; Septiari, Ni Kadek; Listyana, I Gusti Agung Ayu Putu; Rahayu, Ni Komang Ari (Indonesian Journal of Educational Development (IJED), 2025)
Enhancing students' decision-making abilities and reducing cognitive dissonance are critical goals in developing metacognitive awareness and psychological readiness for complex learning tasks. However, conventional learning models often overlook the role of self-regulation and metacognitive control, leading to fragmented reasoning and unresolved internal conflict. This study examines the impact of a metacognitive-based learning approach on students' decision-making skills and levels of cognitive dissonance in an educational setting. A quasi-experimental design was implemented, involving students divided into experimental and control groups. This study used a cluster random sampling technique. The population of this study consisted of elementary school students divided into two groups, namely the control and experimental groups. Data were collected through a validated decision-making assessment and a cognitive dissonance inventory. The data were analyzed using multivariate analysis of variance (MANOVA) to assess the impact of the intervention. The findings revealed that students who participated in metacognitive-based learning significantly outperformed their peers in decision-making tasks and exhibited lower levels of cognitive dissonance. The structured learning cycle focusing on planning, monitoring, and evaluating cognitive strategies enabled students to make more deliberate choices while aligning their beliefs and actions. These results highlight the effectiveness of metacognitive-based learning in fostering cognitive harmony and rational decision-making. The study supports the integration of metacognitive strategies into classroom instruction to promote deeper learning and adaptive cognitive behavior. Future research is recommended to explore the long-term effects of metacognitive-based learning on students' decision-making consistency and cognitive dissonance resolution across diverse educational contexts.